Application of Model Group Investigation based on Experiments Against Student Academic Skills - Rahim, Abd; Nadira, Nadira (International Journal of Education and Teaching Zone, 2022)
This study aims to see the effect of the Experiment-based Group Investigation learning model on the academic skills of students at one of the Madrasah Aliyah Negeri in Tebo. This research is quantitative by using the experimental method. using a posttest-only control group design. This study used two classes, namely the experimental class and the control class, sampling using the cluster random sampling technique. The instruments used for data collection are test questions and observations. Before the data were analyzed, normality and homogeneity tests were first performed. Then, the data were analyzed using a t-test and effect size. Based on the results of the study, it is known that there is an effect of using the Experimental-based Group Investigation learning model on the Academic Skills of students in learning physics. This can be seen from the calculation of the average post-test academic skill score for experimental class students, 78.7 out of 26 students, and the average post-test academic skill score for control class students, 73.7 out of 25 students.